Factors Influencing Self-Regulated Learning Among FKIP Students at Universitas Muhammadiyah Makassar Post-COVID-19 Pandemic - Hafid, Hilda; Ulviani, Maria (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2024)
The aim of this research is to find the dominant factors that influence the Self Regulated Learning (SRL) of prospective teachers during the Covid-19 pandemic and map the level of SRL of prospective teachers in each aspect of SRL. The research method used is a quantitative descriptive method. The instrument used is a questionnaire regarding self-regulated learning. The aspects assessed in the self-regulated learning questionnaire consist of learning strategies, motivation, thinking, performance control and self-reflection. The distribution of the questionnaire was carried out from 3 to 17 May 2024 involving 68 prospective teacher students at one of the private campuses that organize teacher education programs in Makassar City. A total of 68 prospective teachers filled out the survey. Data analysis was carried out using Exploratory Factor Analysis (EFA) with the help of SPSS 23 software. The most dominant factor among the 5 factors is thinking. In this regard, prospective teachers in Makassar City should increase motivation factors, learning strategies, self-reflection and performance control in order to create good learning independence or SRL after the COVID-19 pandemic.